Maire Gullichsen : Fine Arts, design, architecture. - Pori Art Museum, Pori (Pori : Pori Art Museum, 2000)
A documentary cross-section of Professor Maire Gullichsen"s (1907-1990) work as a champion of international modern art and culture in Finland in the 1930's to 1950's. The photographs, art works and objects portray the early stapes of the Free Art School and Artek, as well as Maire Gullichsen's artistic career as a glass designer and painter. In particular the exhibitions concentrates on Maire Gullichsen's influence in the Satakunta region.
Engels
Fins
Zweeds
Maire Gullichsen, Pori Art Museum, Pori, 10.6 - 5.11.2000
boek
Keywords: Gullichsen, Maire; Finland